SELF-CARE MANAGEMENT FROM THE PERSPECTIVE OF HEART FAILURE PATIENTS - Pien, Lee Siew; Binti Mahno, Noor Ezah; Binti Mohd Mokhtar, Hanida Hani (Jurnal Keperawatan dan Kesehatan, 2025)
Background: To explore the understanding of heart failure self-care management among patients. Method: A generic qualitative research design was employed, utilizing the Arabic language version of face-to-face interviews and a purposive sampling technique. A sample of 24 patients treated for heart failure (HF) at a tertiary heart center in the Kingdom of Saudi Arabia was recruited from May 2024 to May 2025. Results: Patients’ perceptions, beliefs, and readiness towards managing heart failure highlighted how limited awareness, emotional denial, and dependency on healthcare providers contributed to the inadequate and inconsistent self-care engagement behavior of the heart failure (HF) patients Conclusion: This study emphasizes the need for HF symptom perception management education programs for patients, continuous professional development for healthcare providers, promotion of positive attitudes, and fostering interdisciplinary collaborations to improve HF self-care management among HF patients. Future research should examine how psychological stress affects coping in heart failure patients, explore organizational roles, and investigate how knowledge, attitudes, and clinical practices contribute to poor self-care, focusing on HCPs and caregivers.